(untitled) (Bangladesh Journal of Neuroscience, 2013)
Background and objectives: Carotid atherosclerosis constitutes an important cause of ischemic stroke. Type 2 diabetes mellitus is known to be an independent risk factor for stroke and its recurrence. This study was aimed to explore relationship between carotid atherosclerosis and ischaemic stroke in patients with diabetes and its association with other risk factors. Materials and Methods: A total number of 50 ischemic stroke patients, as confirmed by CT/MRI, patients with type 2 diabetes mellitus, of both sexes, age range 40-79 years, were recruited in the study from in-patient Neurology department, BIRDEM. Carotid duplex study was done. Ischemic Stroke patients were sub grouped into normal, mild (<2), moderate (2-4) and severe (>4) on the basis of ICA/CCA flow velocity ratio. Blood glucose and fasting lipid levels and blood pressure were recorded. Lipid abnormality ,LDL 130mg/dl, total cholesterol 200 mg/dl was defined following NCEP and AHA guidelines. Data were collected in a pre-formed printed case record form and analyzed using SPSS software. Results: Of the 50 cases only 9 (18%) had normal ICA/CCA flow velocity ratio. Their mean age was 48.0±4.4 years. Three (6%) cases had severe form of ICA/CCA flow velocity ratio 47.67±2.08. Subjects with stroke having mild to moderate compromised flow velocity ratio were significantly older (p<0.001). Mean (±SD) total cholesterol and LDLcholesterol were significantly associated with ICA/CCA flow velocity ratio (p<0.001 for both) in the study subjects. Serum triglyceride did not show significant association with ICA/ CCA flow velocity ratio. Uncontrolled diabetes mellitus (p=0.02) and blood pressure (p=0.001) shown to be significantly associated with atherosclerotic changes in the study subjects. Conclusions: The data conclude that diabetic patients with ischemic stroke have carotid atherosclerosis which is significantly related with lipid abnormality. High total cholesterol and LDL cholesterol are associated with degree of carotid atherosclerosis. Study subjects with severe atherosclerotic changes are relatively younger in age. Carotid duplex study should be planned in ischemic stroke patients with diabetes which will identify the individual at risk and suggest them necessary prevention program. Bangladesh Journal of Neuroscience 2013; Vol. 29 (1) : 24-30